2016
DOI: 10.1177/0961203316664595
|View full text |Cite|
|
Sign up to set email alerts
|

Breast cancer in systemic lupus

Abstract: Objective There is a decreased breast cancer risk in SLE versus the general population. We assessed a large sample of SLE patients, evaluating demographic and clinical characteristics and breast cancer risk. Methods We performed case-cohort analyses within a multi-centre international SLE sample. We calculated the breast cancer hazard ratio (HR) in female SLE patients, relative to demographics, reproductive history, family history of breast cancer, and time-dependent measures of anti-dsDNA positivity, cumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…may increase the risk of certain cancers, such as in the lung (35), others show a reduction or absence of such an association (36). We found no association between HS cancers and oral contraception, the number of pregnancies, or menopause, nor has this association been previously demonstrated with breast cancer (33).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…may increase the risk of certain cancers, such as in the lung (35), others show a reduction or absence of such an association (36). We found no association between HS cancers and oral contraception, the number of pregnancies, or menopause, nor has this association been previously demonstrated with breast cancer (33).…”
Section: Discussioncontrasting
confidence: 57%
“…SLE diagnostic age and period of disease evolution were associated with both HS and non-HS cancers. In other studies, age was associated with cancer in general, in particular with breast cancer and lymphomas (27,33,34). Bernatsky et al (27) have suggested that lupus duration confers a protective effect against cancer onset.…”
Section: Discussionmentioning
confidence: 93%
“…This underlined once again the universal importance of smoking cessation, particularly in chronic autoimmune disorders such as SLE [ 51 ]. Bernatsky et al put forward the hypotheses that breast cancer risk in SLE might be influenced by autoantibody profiles or drug exposures, such as nonsteroidal anti-inflammatory drugs and antimalarial drugs, although no definite associations were ultimately revealed [ 52 ]. As for the increased incidence rate of non-Hodgkin’s lymphoma in patients with SLE, Kang et al proposed that abnormal B-cell function and the use of immunosuppressive agents might lead to lymphoma by direct mutagenesis or by disturbing immune surveillance [ 27 ]; other factors include age, underlying genetic factors, environmental triggers.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell such as T and B and NK lymphocytes express intracellular oestrogen receptors [14]. In this context it is interesting to remember the curious observation that systemic lupus patients had fewer breast cancers than the general population [28]. In lower concentrations it has an opposite action.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that oestrogens enhance the number and function of regulatory T cells (T reg ), suggesting a potential interaction between this hormone and immune regulatory mechanisms [14]. In this context it is interesting to remember the curious observation that systemic lupus patients had fewer breast cancers than the general population [28]. Therefore, the inverse relationship between ANA and oestrogen receptor presence, although interesting, is not clear at present, but certainly deserves further studies.…”
Section: Discussionmentioning
confidence: 99%